Hybrid Nanostructures for Cancer theranostics - Bohara, Raghvendra Ashok; Thorat, Nanasaheb (Micro & nano technologies., 2019)
"Hybrid nanostructures are nanoparticles which incorporate two or more structures. These structures may represent organic or inorganic material, but they synergistically improve the application of the material for end users. Hybrid Nanostructures for Cancer Theranostics explores how hybrid nanostructures are used in cancer treatment. Focusing on the properties of hybrid nanostructures, the book demonstrates how their unique characteristics can be used to create more effective treatment techniques. In the second half of the book, the chapters examine how hybrid nanostructures are currently being used in practice, assessing the pros and cons of using different types of nanostructures for different treatments. This valuable resource will allow readers to understand the core and emerging concept of functionalization, bioconjugation, hyperthermia and phototherapy of nanoparticles which allows for the greater use of hybrid nanomaterials in cancer theranostics. Shows how the use of novel hybrid nanostructures can lead to more effective cancer treatments. Explores how hybrid nanostructures are used for different treatment types, including photo thermal therapy and drug delivery. Explains how the use of hybrid nanostructures can lead to more rapid cancer diagnosis."--